Co-Digestion of Three Types of Manure (Cow, Guinea Pig and Pig) to Obtain Biogas in Southern Peru - Barreda Del Carpio, Jaime Ernesto (2022)
The lack of energy in rural areas is a problem that mainly affects developing countries. Efficient and sustainable alternatives are currently being sought that can solve this problem. The present investigation evaluated the volumetric production and biogas composition of 12 mixtures of three types of substrates (cow, pig and guinea pig manure), the substrates were characterized to know their percentage of moisture, ashes, organic matter, Kjeldahl nitrogen, C/N ratio and total metals, then the volumetric production of biogas was evaluated for 23 days in each system in triplicate and finally the composition of the biogas was analyzed, the contents of organic matter, nitrogen and C/N ratio were very similar to that reported by several authors, in the three substrates the presence of heavy metals such as copper and nickel was observed, only in cow manure was lead observed, on the other hand the presence of trace elements that are beneficial for anaerobic digestion such as selenium was also observed in guinea pig manure. The system that generated the highest volume of biogas was system S3, which contained 25% cow manure, 25% pig manure and 50% guinea pig manure, producing 33.6 ± 0.42% methane. The volumetric production and percentage of methane in the biogas was directly affected by the presence of metals that inhibit or slow down the development of methanogenic microorganisms.